PENDIDIKAN AGAMA ISLAM ANAK BROKENHOME: PERAN EXTENDED FAMILY - Daulay, Lily Sardiani; Sit, Masganti; Rakhmawati, Fibri (JURNAL TARBIYAH, 2024)
This research explores the role of the extended family in providing Islamic religious education to children from broken homes. The research method used is descriptive qualitative using interview and observation data collection techniques. The results of this research are that the reason extended families are actively involved in religious education is because of the busyness and indifference of biological parents, as well as to prevent children from falling into promiscuity. The process of implementing religious education carried out by the extended family is that they teach prayer, reciting the Koran, religious values, sex education, and dress ethics through direct methods, media such as animated videos, and discussions. The extended family experience shows pride in children's development, despite challenges such as laziness and child denial. To overcome this challenge, lecture methods, punishment and reward systems are used. The observation results show the active involvement of children in religious activities, as well as the implementation of an effective punishment and reward system. This research highlights the important role of extended families in providing Islamic religious education to children from broken homes. However, to increase the effectiveness of this education, further research is recommended that focuses on empowering extended families through educational management training for children from broken homes. This training can help extended families develop better skills and strategies in educating and caring for their children.